The clinical applications of perforator flaps based on the ulnar artery - Omar Ahmed Gamil Elsharkawy; Husam Eddin Hosny Abdulwahab; Maamoun Ismail Maamoun; Mohamed Mahmoud Eleissawy (Cairo : Omar Ahmed Gamil Elsharkawy, 2014)
The repair of complicated wounds in the upper limb continues to represent a challenging problem to the reconstructive surgeon. Various studies have been published on radial artery perforator flaps. However, ulnar artery perforator flaps have not been researched as much. The goal of this study was to assess the clinical applications of ulnar artery based perforator flaps. In this study there were 19 cases with various defects over the hand, wrist, forearm and elbow. Ulnar artery perforators were located by doppler and duplex ultrasonography. Perforator location was confirmed and recorded intraoperatively. Based on perforator location, various flaps were designed to cover the defects. Stable coverage was achieved in 18 cases, while 1 case suffered total loss of the flap. Five cases showed partial loss of the flap that did not affect the final outcome. Two cases suffered wound infection
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Freestyle flaps; Perforator flaps; Ulnar artery